2014
DOI: 10.4168/aair.2014.6.6.496
|View full text |Cite
|
Sign up to set email alerts
|

Novel genes in Human Asthma Based on a Mouse Model of Allergic Airway Inflammation and Human Investigations

Abstract: PurposeBased on a previous gene expression study in a mouse model of asthma, we selected 60 candidate genes and investigated their possible roles in human asthma.MethodsIn these candidate genes, 90 SNPs were genotyped using MassARRAY technology from 311 asthmatic children and 360 healthy controls of the Hungarian (Caucasian) population. Moreover, gene expression levels were measured by RT PCR in the induced sputum of 13 asthmatics and 10 control individuals. t-tests, chi-square tests, and logistic regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Asthma has an estimated heritability of more than 60% [ 3 , 4 ], but in accordance with the considerable immunological and phenotypical variation, it is genetically heterogenous [ 5 ] and more than 200 genes have been shown to be related to asthma [ 6 ]. Furthermore, there are also important environmental risk factors, including indoor and outdoor allergens, such as mites or pollens, and irritants like lipopolysaccharides (LPS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma has an estimated heritability of more than 60% [ 3 , 4 ], but in accordance with the considerable immunological and phenotypical variation, it is genetically heterogenous [ 5 ] and more than 200 genes have been shown to be related to asthma [ 6 ]. Furthermore, there are also important environmental risk factors, including indoor and outdoor allergens, such as mites or pollens, and irritants like lipopolysaccharides (LPS).…”
Section: Introductionmentioning
confidence: 99%
“…Animal, predominantly murine, models are extensively studied to improve our understanding of the complex immunogenetic background of asthma [ 6 ]. However, murine models have important limitations, since mice have a short life span and do not spontaneously develop asthma, but must undergo sensitization protocols with allergen challenges [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both neovascularization and angiogenesis are also remarkable features of asthma causing structural changes in the airway walls. Increased vascularity and angiogenesis in asthmatic patients contribute to airway occlusion as a result of an increase in airway wall thickness (Temesi et al, 2014;Fodor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bronchial asthma is defined by the history of respiratory symptoms such as wheeze, shortness of breath, chest tightness and cough that vary over time and in intensity, together with variable expiratory airflow limitation [2]. Previously published evidence suggested that both environmental components and genetic variations may contribute to asthma susceptibility [3]. The major mast cell growth factor, stem cell factor (SCF) is a cytokine that may contribute to the inflammatory changes occurring in diseases associated with an increased mast cell number and activation, like asthma [4].…”
Section: Introductionmentioning
confidence: 99%